C-Phycocyanin as a potential biosensor for heavy metals like Hg2+ in aquatic systems. Issue 112 (24th November 2016) - Bhayani, Khushbu; Mitra, Madhusree; Ghosh, Tonmoy; Mishra, Sandhya
Abstract : Fluorescence quenching ability of C-phycocyanin (CPC) as a biosensor for detection of Hg 2+ in lower concentrations (μM) in aquatic environment. Abstract : The purpose of this study is to exploit the fluorescence quenching ability of C-phycocyanin (CPC) with heavy metals, establishing it as a biosensor specifically for the detection of Hg 2+ even in lower concentrations (μM) in polluted water containing various metals. In this work, we have compared the fluorescence quenching of C-phycocyanin upon binding with 12 different metal ions (Cr 3+, Zn 2+, Fe 2+, Mg 2+, Ni 2+, Pb 2+, Cu 2+, Hg 2+, Co 2+, Ca 2+, Ag + and Li + ). The binding efficiency and intensity of fluorescent quenching were investigated using fluorescent spectral studies. Fluorescence quenching data clearly demonstrate that the fluorescence quenching effect with different metals on the C-phycocyanin are in the order Hg 2+ > Cu 2+ > Ag + > Pb 2+ > Cr 3+ . The decrease of fluorescence intensity is proportional to the concentration of Hg 2+, which is further confirmed by spectral analysis using FT-IR spectroscopy. FT-IR analysis revealed that C-PC–Hg 2+ interactions resulted in conformational changes in CPC. Changes in the secondary structure of CPC were confirmed by CD spectral analysis. The ITC results also corroborate the higher binding of Hg 2+ with CPC shown from the higher Gibbs free energy value among the metal ions studied. Thus, CPC could be further utilized as a selective and sensitive biosensor for the detection of perilous Hg 2+ in the environment.